Analisis Pengendalian Internal atas Prosedur Pencairan Piutang Leasing pada Perusahaan Tridjaya Motor Cabang Kota Manado - Nova Pebriani Silelek; Anita L.V Wauran; Shane Anneke Pangemanan (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study aims to analyze internal controls over the procedures for collecting lease receivables at the Tridjaya Motor Branch in Manado. The study employs a qualitative descriptive method, with data collected through observation, interviews, and documentation. The analysis was conducted based on the five components of internal control according to COSO, namely the control environment, risk assessment, control activities, information and communication, and monitoring. The results of the study indicate that the procedures for the settlement of lease receivables have been implemented in a structured manner through the segregation of duties between the sales and administrative departments, the use of complete supporting documents, and a multi-level authorization system. However, several challenges were identified, such as role overlap due to limited human resources, delays in interdepartmental communication, data entry errors, and delays in document verification by the leasing party. These conditions resulted in delays in fund disbursement and affected the company’s cash flow stability. Therefore, the company needs to improve coordination, supervision, and routine evaluation to ensure that internal control effectiveness operates more optimally.